Association of preceding psychosis risk states and non‐psychotic mental disorders with incidence of clinical psychosis in the general population: a prospective study in the NEMESIS‐2 cohort. Issue 2 (11th May 2020) - Guloksuz, Sinan; Pries, Lotta‐Katrin; ten Have, Margreet; de Graaf, Ron; van Dorsselaer, Saskia; Klingenberg, Boris; Bak, Maarten; Lin, Bochao D.; van Eijk, Kristel R.; Delespaul, Philippe; van Amelsvoort, Therese; Luykx, Jurjen J.; et al.
Abstract : The validity and clinical utility of the concept of "clinical high risk" (CHR) for psychosis have so far been investigated only in risk‐enriched samples in clinical settings. In this population‐based prospective study, we aimed – for the first time – to assess the incidence rate of clinical psychosis and estimate the population attributable fraction (PAF) of that incidence for preceding psychosis risk states and DSM‐IV diagnoses of non‐psychotic mental disorders (mood disorders, anxiety disorders, alcohol use disorders, and drug use disorders). All analyses were adjusted for age, gender and education. The incidence rate of clinical psychosis was 63.0 per 100, 000 person‐years. The mutually‐adjusted Cox proportional hazards model indicated that preceding diagnoses of mood disorders (hazard ratio, HR=10.67, 95% CI: 3.12‐36.49), psychosis high‐risk state (HR=7.86, 95% CI: 2.76‐22.42) and drug use disorders (HR=5.33, 95% CI: 1.61‐17.64) were associated with an increased risk for clinical psychosis incidence. Of the clinical psychosis incidence in the population, 85.5% (95% CI: 64.6‐94.1) was attributable to prior psychopathology, with mood disorders (PAF=66.2, 95% CI: 33.4‐82.9), psychosis high‐risk state (PAF=36.9, 95% CI: 11.3‐55.1), and drug use disorders (PAF=18.7, 95% CI: –0.9 to 34.6) as the most important factors. Although the psychosis high‐risk state displayed a high relative risk for clinical psychosis outcome even after adjusting for other psychopathology, the PAF was comparatively low, given the low prevalence of psychosis high‐risk states in the population. These findings provide empirical evidence for the "prevention paradox" of targeted CHR early intervention. A comprehensive prevention strategy with a focus on broader psychopathology may be more effective than the current psychosis‐focused approach for achieving population‐based improvements in prevention of psychotic disorders.